2021
DOI: 10.7150/thno.55946
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics study reveals that statin therapy is associated with restoration of gut microbiota homeostasis and improvement in outcomes in patients with acute coronary syndrome

Abstract: Rationale: Prior chronic treatment with statins has been shown to be associated with more favorable outcomes in patients with acute coronary syndrome (ACS). Specific changes in the gut microbiota and microbial metabolites have been shown to influence the progression of coronary artery disease. However, the critical microbial and metabolomic changes associated with the cardiovascular protective effects of statins in ACS remain elusive. Methods: In the present study, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 69 publications
0
37
0
Order By: Relevance
“…Studies from animal or human cohorts have found that using statins profoundly alters the gut microbiota profile. Though the featured microbiota changes induced by statins are yet to be characterized, most studies linked the altered gut microbiota composition to positive therapeutic responses of statins on CAD outcomes (Khan et al, 2018;Kim et al, 2019;Dias et al, 2020;Kummen et al, 2020;Vieira-Silva et al, 2020;Hu et al, 2021). A recent report, however, revealed the negative side of statin-induced microbiota changes, which reduced fecal butyrate and increased secondary bile acid production in a PXR-dependent manner (Caparros-Martin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from animal or human cohorts have found that using statins profoundly alters the gut microbiota profile. Though the featured microbiota changes induced by statins are yet to be characterized, most studies linked the altered gut microbiota composition to positive therapeutic responses of statins on CAD outcomes (Khan et al, 2018;Kim et al, 2019;Dias et al, 2020;Kummen et al, 2020;Vieira-Silva et al, 2020;Hu et al, 2021). A recent report, however, revealed the negative side of statin-induced microbiota changes, which reduced fecal butyrate and increased secondary bile acid production in a PXR-dependent manner (Caparros-Martin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the genera level, Parabacteroides and Sutterella were increased in the IBS group compared to the control group and the IBS + Bi co group. Parabacteroides and Parabacteroides merdae (belongs to Parabacteroides genera) were considered as potentially pathogenic bacterium that were reported to be frequently enriched in the hypertensive gut microbiome [45,46]. Moreover, in infectious diseases, Parabacteroides merdae is generally considered an opportunistic pathogen, which is able to develop antimicrobial drug resistance [47].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial DNA was isolated from fecal samples by using the bead-beating method. The DNA extracted from each sample was used as the template to amplify the V3-V4 region of 16S rRNA gene by using PCR (Phusion High-Fidelity PCR Master Mix with GC Buffer, from New England Biolabs Company), which were illustrated in our previous publication ( 24 ). Raw data quality control was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The purified products were mixed at an equal ratio for sequencing using an Illumina MiSeq system (Illumina Inc., USA). The detailed method refers to our previous study ( 24 ).…”
Section: Methodsmentioning
confidence: 99%